Návrh strategie rozvoje malé rodinné firmy - Teturová, Darina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Bakalářská práce se zabývá stanovením návrhu rozvoje podniku. Vychází z tržních příležitostí, silných a slabých stránek vinařství. Analyzuje vnitřní a vnější prostředí podniku. Návrh dalšího rozvoje vychází ze shromážděných informací a vytvořených analýz.

This bachelor thesis deals with a determination of the company development. It is based on market opportunities, strengths and weaknesses of the winery company and analyzes internal and external business environment. Proposal for further development of the company is based on information gathered and developed in analyzes.
The Proposal of the Small Family Business Strategy Development
Keywords: Strategie; vinařství; rozvoj podniku; marketingový mix; podnikatelský plán; projekt; výrobková řada.; Strategy; winery; business development; marketing mix; business plan; project; product line.